Transformative leadership in action : allyship, advocacy & activism - Bruce, Jacklyn A.; McKee, Katherine E. (Building leadership bridges., 2020)
In a time when the world is facing significant challenges, leaders who work for justice and equity for all people are necessary. Transformative Leadership in Action: Allyship, Advocacy, and Activism challenges the reader to do the essential self-work required of a 21st century leader, and provides the road map to developing the skills necessary to take on increasing public leadership roles to support causes related to justice and equity. Shining a light on unexplored, yet crucial, components of the discussion around the apex of leadership and social justice, Bruce and McKee first investigate the tie between social justice work and leadership competencies grounded in theory. Second, they put forward a pedagogical guide in teaching at this apexengaging both the instructor and student(s) in unique learning journeys. Offering insight for educators, current leaders, and future leaders, this book is a crucial resource - providing go-to support for engaging in allyship, advocacy, and activism for justice and equity. If you want your learners to be leaders and not just think about leadership, this is the book you need.